PENGEMBANGAN MODUL PEMBELAJARAN BAHASA INDONESIA BERBASIS CHATGPT FOKUS KETERAMPILAN MENULIS KELAS V SD NEGERI DI DABIN 1 KECAMATAN AMPELGADING - Pitta Danuwindah Nareswari; Rahmad Agung N; Basukiyatno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Developing students' communication skills in Indonesian language learning, particularly in writing, plays a fundamental role. However, mastering specific genres of writing, such as summarizing or creating expository texts, often poses a significant challenge at the elementary school level. Conventional teaching approaches are frequently unable to arouse student interest and facilitate deep understanding, which leads to low motivation and suboptimal learning outcomes. In response to these problems, this study aims to design an Indonesian language learning module based on ChatGPT, focusing on writing skills for fifth-grade students at SD Negeri in Dabin 1, Ampelgading District. This research uses the Research and Development (R&D) method with the 4D model, limited to the